Genetic variations of strawberry cultivars of Fragaria x ananassa and Fragaria vesca based on RAPD - GANIES RIZA ARISTYA; RINA SRI KASIAMDARI; RACHMI SETYONINGRUM; BENING LARASATI (Society for Indonesian Biodiversity, 2019)
Abstract. Aristya GR, Kasiamdari RS, Setyoningrum R, Larasati B. 2019. Genetic variations of strawberry cultivars of Fragaria x ananassa and Fragaria vesca based on RAPD. Biodiversitas 20: 770-775. In Indonesia, the increasing market demand for strawberries (Fragaria spp.) is not comparable to increased strawberry productivity. One of the efforts made to increase strawberry productivity with superior quality is plant breeding. The purpose of this research was to determine the genetic variation, lineage, and similarity index in some strawberry cultivars using molecular markers of Random Amplified Polymorphic DNA (RAPD). Eleven strawberry cultivar samples were taken from Indonesian Citrus and Subtropical Fruits Research Institute (Balitjestro), Batu City, East Java, Indonesia and Strawberry Agritourism in Banyuroto Village, Magelang District, Central Java, Indonesia. DNA isolation using modified CTAB buffer method. DNA amplification using PCR-RAPD method with 5 primers, namely UBC-516, UBC-594, OPA 10, OPA 16, and OPG 11. Strawberry lineage dendrogram construction was analyzed with clustering of Unweight Pair-Group Using Arithmetic Average (UPGMA) software Multi-Variate Statistical Average (MVSP). The research results showed that the 5 RAPD primers used in 11 strawberry cultivars produced 30 polymorphic DNA bands and 20 monomorphic DNA bands so it can be concluded that the genetic variation among 11 strawberry cultivars can be detected using RAPD molecular markers. The lineage of 11 strawberry cultivars that have the highest similarity index is found in Earlibrite and Rosalinda II cultivars of 98.85%.